USING THE GEOGEBRA SOFTWARE IN CREATING FUNCTION GRAPHS - Nigora Alisherovna Umarova (Web of Journals Publishing, 2024)
The article talks about the use of Geogebra software for creating function graphs.
Keywords: geogebra, shadow, horizon line, perspective, numerical scale, construction stages.